Sociologies of Resilience - Purkayastha, Bandana (Espacio Abierto, 2025)
The Global North lineage of the concept resilience has ranged from security studies, and other discussions that focus on individuals becoming responsible for getting through difficult times.  The critics have pointed to the ways in which the state and other institutional culpability for creating crises is wiped out through this neo-liberal individual-responsibility focused approach.  Even refugees, whose lives devastated by war and other human made conflict, traditionally seen as deserving of humanitarian aid, are being asked to develop resilient, individual-level solutions to the crises that envelop them.  Sociologists are also aware of resilience that develops through activism and protests, including shared meaning-making where resilience is an ingredient of resistance.   This paper outlines these strands of scholarly conversations.  It also looks at the concept of resilience from the perspective of knowledge hierarchies and emphasizes the need to expand our methodologies to become more sensitive to multiple ways in which resilience is expressed around the world without the use of this English-rooted term